1998
DOI: 10.1002/(sici)1097-4628(19980531)68:9<1485::aid-app11>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of gelatin-N-vinylpyrrolidone graft copolymer

Abstract: ABSTRACT:The graft copolymerization of N-vinylpyrrolidone (VP) onto gelatin was carried out by the following four different initiator systems: AIBN, K 2 S 2 O 8 , H 2 O 2 {Fe 2/ , and Ce 4/ {HNO 3 . The last one caused the monomer to lose the doublebond and polymerization ability due to the hydrolysis of the monomer. Using a,aazobisisobutyronitrile as an initiator, the graft copolymerization of gelatin and N-vinylpyrrolidone in aqueous medium was studied systematically. The relationships between the rate of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Figure 1 shows a possible reaction between NaAlg and N-VP. Similar graft copolymerization of N-VP has been reported by Gao et al 23 They studied grafting of N-VP onto gelatin with four initiator systems which are AIBN, potassium persulfate, peroxide-ferrous, and cerium ammonium nitrate and they found that initiating ability of the AIBN is better than other initiators in the graft polymerization. Graft polymerization studies using AIBN initiator onto carboxymethyl cellulose were also investigated in the earlier study.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Figure 1 shows a possible reaction between NaAlg and N-VP. Similar graft copolymerization of N-VP has been reported by Gao et al 23 They studied grafting of N-VP onto gelatin with four initiator systems which are AIBN, potassium persulfate, peroxide-ferrous, and cerium ammonium nitrate and they found that initiating ability of the AIBN is better than other initiators in the graft polymerization. Graft polymerization studies using AIBN initiator onto carboxymethyl cellulose were also investigated in the earlier study.…”
Section: Resultssupporting
confidence: 64%
“…20 Biocompatible polymeric hydrogels has been effectively used for controlled release systems. Many worker have carried out grafting reactions of N-VP onto silica, 21 polypropylene film, 22 gelatin, 23 and low density polyethylene. 24 However, grafting of hydrophilic N-VP onto NaAlg and controlled release application of it has not been studied up to now.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the effects of grafting monomers, initiators, and reaction conditions on the percentage of grafting (G%) and the grafting efficiency have been studied systematically 5–8. However, there are few reports about the swelling behavior of graft copolymers,9 and no study on the swelling kinetics of gelatin graft copolymers has been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Graft copolymerization is one of the most effective ways to improve the comprehensive properties of polymer materials, and it is especially suitable for natural macromolecules such as cellulose, 6 gelatin, 7,8 starch, 9,10 pullulan, 11 and chitosan. 12,13 Generally, free-radical initiators used for synthetic polymerization can be applied to the graft modification of starch; 14 common initiators such as peroxide and redox systems are often used in the graft copolymerization of natural macromolecules.…”
Section: Introductionmentioning
confidence: 99%